Bacterias autótrofas y heterótrofas asociadas a nieve marina lodosa en arrecifes con escorrentía continental - Henao-Castro, Alejandro (2014)
The density of heterotrophic bacteria is greater than autotrophic in marine snow aggregates influenced by continental runoff. Four coral reef areas at different distances from the Canal del Dique served to evaluate this premise; this canal is the main source of inland resources for the coral reefs of the Nuestra Señora del Rosario archipelago in Cartagena in the Colombian Caribbean. The average density of microorganisms in marine snow aggregates was determined using epifluorescence. The results showed higher density of heterotrophic bacteria (3.63 x 104 ± 1.6 x 104 SE cells mL-1) than autotrophic (6 x 103± 1.3 x 103 SE cells mL-1), mainly in reefs near continental runoff discharges (heterotrophic bacteria density of 8.9 x 104 cells mL-1 and 3 x 104 cells mL-1 Isla Arena and Tesoro, respectively). The density of microorganisms found is typical of high-particulate organic matter areas and, therefore, could be a potential indicator of continental runoff. Future studies should focus on determining the composition of the bacterial community associated with marine snow and its potential virulence on reef organisms.